Übergangsprozesse von der Schule in die Erwerbstätigkeit in Japan und Deutschland im Kontext von Beruflichkeit und Stratifizierung - Pilz, Matthias [Verfasser]; Alexander, Peter-Jörg [Verfasser] (My University, 2007)
"The transition process from school into employment is a well known research object in international comparisons. This article will focus on two special issues. On the one hand this will be the comparison between Japan and Germany, two countries with very different (vocational) education systems and labour market entry regulations. On the other hand it will focus on two different aspects in the transition process: One is the role of 'vocationalism' (Berufskonzept) and the other is the stratification in the systems of education and training. For Japan an indirect type of stratification and no vocationalism can be found. In contrast to that a direct type of stratification is very common in Germany and vocationalism plays a major role in the transition process. Japan, however, even without direct stratification and vocationalism is very successful in managing the transition process. Here the high ratio of academic education, the relatively unspecific vocational education combined with expanded internal training after entering a company as well as the yet important close link between the employee and the company are important factors." (Author's abstract, BIBB-Doku)
Keywords: G 1.3.2.2.3 Zweite Schwelle, in Arbeit; T 1.5 International vergleichende Berufsbildungsforschung; I 2.1 Deutschland; I 2.3.4 Asien; Berufseinmündung; Zweite Schwelle; Berufsbildungssystem; Beziehung Bildungssystem Beschäftigungssystem; Beruflichkeit; Soziale Schichtung; Internationaler Vergleich; Bundesrepublik Deutschland; Japan